Beating IT risks - Jordan, Ernie (J. Wiley, 2005)
"Beating IT Risks is the essential guide for managers at risk from information technology failures. It provides proven models and evaluation tools that will guide board members, senior management, IT leaders and business unit managers in their decision-making, monitoring and negotiation roles. This book will also be a valuable resource for those studying this topic on IT and Risk Management courses."--Jacket.